2008
DOI: 10.1161/hypertensionaha.108.117630
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D Levels and Risk of Incident Hypertension Among Young Women

Abstract: Abstract-Numerous 5 and various locations in the kidney. 6 -9 Experimental studies demonstrate that 1,25(OH) 2 D inhibits renin expression, 4,10 enhances insulin secretion and sensitivity, 11,12 and blocks proliferation of VSMCs. 13 Although cross-sectional studies demonstrate that 25(OH)D levels, and skin exposure to UVB radiation (the major source of vitamin D), 14,15 are associated with lower blood pressure, 16 -22 prospective data are limited. An interventional study conducted in 148 vitamin D-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
244
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(283 citation statements)
references
References 35 publications
14
244
4
6
Order By: Relevance
“…One study reported no association between serum 25OHD and future hypertension or change in blood pressure, 17 whereas other studies demonstrated a positive association between plasma 25OHD and risk of developing hypertension. 36,37 The lack of association between vitamin D status and blood pressure might be attributable to the relatively high baseline levels of serum 25OHD among the participants in these studies, as in our study. 18 To our knowledge, only one study has been conducted to examine the association between plasma 25OHD and blood pressure in Chinese.…”
Section: -O76mentioning
confidence: 49%
“…One study reported no association between serum 25OHD and future hypertension or change in blood pressure, 17 whereas other studies demonstrated a positive association between plasma 25OHD and risk of developing hypertension. 36,37 The lack of association between vitamin D status and blood pressure might be attributable to the relatively high baseline levels of serum 25OHD among the participants in these studies, as in our study. 18 To our knowledge, only one study has been conducted to examine the association between plasma 25OHD and blood pressure in Chinese.…”
Section: -O76mentioning
confidence: 49%
“…History of kidney stones, hypertension, diabetes mellitus, gout, or thiazide use was obtained from the biennial questionnaires. The validity of self-reported history of kidney stones, hypertension, diabetes mellitus, and gout has been documented previously (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Ascertainment Of Other Factorsmentioning
confidence: 91%
“…In a nested case-control study, in which basal 25(OH) vitamin D and development of incident hypertension were investigated, Forman et al (16) found that among women who developed hypertension, serum uric acid and PTH were higher and 25(OH) vitamin D levels were lower compared with those women who remained normotensive. The latter two studies only recruited women.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%